2019
DOI: 10.1111/joor.12836
|View full text |Cite
|
Sign up to set email alerts
|

Associations between tooth loss, prostheses and self‐reported oral health, general health, socioeconomic position and satisfaction with life

Abstract: Objectives To investigate whether the location of tooth loss and prosthesis are associated with self‐reported oral health, general health, socioeconomic position and satisfaction with life. Methods From the Copenhagen Aging and Midlife Biobank (CAMB) investigation, 1517 persons had their oral status ranked (full dentition, fixed prosthesis in the masticatory zone, tooth loss in the masticatory zone, fixed prosthesis in the aesthetic zone, removable prosthesis, tooth loss in the aesthetic zone). Self‐reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
10
0
6
Order By: Relevance
“…Patients with periodontitis are more likely to have halitosis than those without 4 and at higher risk of developing tooth loss, which could lead to various issues, such as difficulties in mastication and pronunciation of certain sounds, undesirable facial aesthetics, and poor cognitive functions. [5][6][7][8] Unknown to many non-dentists, evidence shows that periodontal disease is associated with several systemic conditions, such as diabetes, cardiovascular disease, and adverse pregnancy outcomes. 9 The periodontal-systemic disease connection is believed to be caused by the metastatic spread of microorganisms and their by-products in dental plaque and inflammatory mediators from periodontal tissues to other organs of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with periodontitis are more likely to have halitosis than those without 4 and at higher risk of developing tooth loss, which could lead to various issues, such as difficulties in mastication and pronunciation of certain sounds, undesirable facial aesthetics, and poor cognitive functions. [5][6][7][8] Unknown to many non-dentists, evidence shows that periodontal disease is associated with several systemic conditions, such as diabetes, cardiovascular disease, and adverse pregnancy outcomes. 9 The periodontal-systemic disease connection is believed to be caused by the metastatic spread of microorganisms and their by-products in dental plaque and inflammatory mediators from periodontal tissues to other organs of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that edentulism had a negative impact on the quality of life of patients, which are in agreement with some previous studies. [17][18][19][20] It was also found that the patients expressed wide range of emotions on losing the teeth from anger to being sad or depressed. However, some patients expressed a sense of relief probably due to the amount of pain they had to bear before the loss of the tooth.…”
Section: Discussionmentioning
confidence: 95%
“…Material e Métodos: O estudo foi realizado em 70 indivíduos que se apresentaram ao Department of Prosthetic Dental Sciences. Foi distribuído um questionário e os dados analisados estatisticamente no SPSS versão 18.0 e valores inferiores a 0,05% foram considerados estatisticamente significativos. Resultados: A dificuldade do participante em aceitar a perda de seu dente anterior, constrangimento e confiança mudaram significativamente após usar a prótese (P <0,05).…”
Section: Introductionunclassified
“…Likewise, it is projected that tooth loss will continue to be a major dental problem in the next decades, which might impair patients general health and cause disabilities 17 . Not only complete edentulism but a reduced number of teeth is directly related to quality of life worsening, since it can compromise daily activities, such as chewing, nutrition, phonation, social life, and self-esteem 18,19 .…”
Section: Discussionmentioning
confidence: 99%